Local Extremums of Trigonometric Polynomial - Belov, I. S. (Журнал математичної фізики, аналізу, геометрії, 2007)
Local extremes of the trigonometric polynomial B_n(θ)=_k=n^k=2nkθkare considered, and various inequalities between them are proved. In particular, the greatest and the least values of B_n(θ) are found. Mathematics Subject Classification: 26A09.